Application of Shell Washing Machine to Improve Hygiene of Fishermen Groups in Tambakrejo Semarang - Subekti, Niken; Maulana, Sonika; Rifa'atunnisa, Rifa'atunnisa; Juhadi, Juhadi; Rozi, Fahrur; Setyanto, Heru (Universitas Negeri Semarang, 2025)
Increasing public awareness in Tambakrejo, North Semarang for improve the quality, hygiene and income of the group fisherman from cultivation shellfish. The presence of fishermen in the area oyster harvest done in a way traditional without use machine, then a group of fishermen was created The King to be able to process Hygienic and quality shellfish .​ The technological transformation that was developed is improve the hygiene and quality of shellfish by using manufacturing technology machine washer shellfish. Downstream research results from the UNNES Team. Machine application technology washer shell For improve hygiene and income fisherman so that in accordance with need market and energy efficiency. Application of machines washer shell is a new innovation technology for downstreaming products from UNNES research team. Machine manufacturing technology washer shellfish, can increase fishermen's income, improve the quality of shellfish green and energy efficiency. Machine manufacturing Shellfish washing is a new innovative technology for downstreaming products resulting from research by the Community Service team. UNNES. During the activity, mentoring and monitoring evaluation were carried out to measure target achievement.